Daya Saing dan Trend Ekspor Teripang Indonesia - P., Rahma Ayunda (Department of Agribusiness, Faculty of Science and Technology, UIN Syarif Hidayatullah Jakarta, 2023)
Indonesian waters as a country that has large areas of coral reefs, so that Indonesia has a variety of marine products, one of which has high economic value, namely sea cucumbers. Production of sea cucumbers in Indonesia continues to increase but only relies on marine catches causing unstable sea cucumber production. The stipulation of COP 18 CITES which regulates the protection, preservation and utilization of several types of sea cucumbers whose circulation is restricted based on volume. One of them is the black milk sea cucumber (Holothuria whitmaei) which can be found in Indonesian waters.This study analyzes the export competitiveness of sea cucumbers to the main destination countries, namely China, Hong Kong, South Korea, and Singapore and analyzes the export trend of Indonesian sea cucumbers for forecasting the next 10 years. The scope of research includes sea cucumbers with HS code 160561. The methods used are RCA, EPD and linear trend.The results of research using the RCA method in China have an average value of 1.27 which has a comparative advantage and Hong Kong, South Korea and Singapore do not have a comparative advantage. The EPD method shows that Indonesian sea cucumbers are in the Falling Star position in the four main destination countries. In the linear trend analysis, the export value of Indonesian sea cucumbers has increased (positive) and the export value of Indonesian sea cucumbers is predicted to continue to increase. The trend value is positive and indicates a positive development cycle movement which means that Indonesia's sea cucumber exports still have the opportunity to increase for the next ten years.AbstrakPerairan Indonesia memiliki wilayah terumbu karang yang luas, sehingga Indonesia memiliki keanekaragaman hasil laut, salah satunya yang memiliki nilai ekonomi tinggi yaitu teripang. Produksi teripang di Indonesia terus meningkat namun hanya mengandalkan hasil tangkap laut menyebabkan produksi teripang tidak stabil. Ditetapkannya COP 18 CITES yang mengatur perlindungan, pelestarian, dan pemanfaatan beberapa jenis teripang tangkap laut dibatasi peredarannya berdasarkan volume. Salah satunya terdapat teripang susu hitam (Holothuria whitmaei) yang dapat ditemukan di perairan Indonesia .Penelitian ini menganalisis daya saing ekspor teripang ke negara tujuan utama yaitu China, Hongkong, Korea Selatan, dan Singapura serta menganalisis trend ekspor teripang Indonesia untuk peramalan 10 tahun kedepan. Ruang lingkup penelitian mencakup teripang dengan kode HS 160561. Metode yang digunakan adalah RCA, EPD dan trend linier.Hasil penelitian dengan metode RCA pada negara China nilai rata-rata 1,27 memiliki keunggulan komparatif dan pada Hongkong, Korea Selatan, dan Singapura tidak memiliki keunggulan komparatif. Metode EPD menunjukan teripang Indonesia terdapat pada posisi Falling Star pada ke empat negara tujuan utama. Pada analisis trend linier nilai ekspor teripang Indonesia meningkat (positif) dan nilai ekspor teripang Indonesia diramalkan akan terus meningkat. Nilai trend yang positif dan menunjukkan pergerakan siklus perkembangan yang positif yang berarti ekspor teripang Indonesia masih berpeluang meningkat untuk sepuluh tahun kedepan.